Pengaruh Pendidikan dan Pelatihan terhadap Kinerja Pegawai dengan Motivasi Belajar Sebagai Variabel Intervening pada Sekolah Polisi Negara (SPN) Polda NTB - Fikri, Ahmad Taupan; Hadiyati, Ernani; Muawanah, Umi (Universitas Batanghari, 2025)
The purpose of this study is to examine how training and education affect worker performance at the State Police School (SPN) Polda NTB, using learning motivation as an intervening variable. This study employs survey-based quantitative methodologies. Employees of SPN Polda NTB who had taken part in the education and training program made up the research sample. To investigate the direct and indirect effects of variables, data were gathered using questionnaires and analyzed using path analytic techniques. The analysis revealed that training had a considerable impact on employee performance at the State Police School (SPN) Polda West Nusa Tenggara, whereas education had no discernible influence. The best model was obtained with an r-square of 91.1%. Furthermore, it has been demonstrated that learning motivation improves worker performance. The relationship between education and training and performance is mediated by learning motivation, which is an intervening variable. Good training and education will raise learning motivation, which will enhance employee performance. According to this study, enhancing the caliber of training and education initiatives and paying more attention to learning motivation are crucial for raising employee performance at SPN Polda Nusa Tenggara Barat.